Performance Comparison Between Different Optimization Techniques in Cognitive Radio for Spectrum Allocation - Sofia, D. Sumithra; Edward, A. Shirly (Wireless personal communications, 2022)
Dynamic spectrum sharing is a distributive opportunistic spectrum access for wireless users to access the spectrum any time dynamically. This proposed approach provides a spectrum allocation technique to the users based on a multi-objective genetic optimization algorithm in interweave mode of spectrum sharing. The multiple objectives targeted are minimizing BER, minimizing Power consumption, and maximizing the Throughput and minimizing interference. This proposed algorithm is compared with the existing Brute force algorithm and provides a gradual increase in the fitness value for an increase in the transmission BW. Also, this proposed algorithm finds better solution to multi-objective scenario with high fitness score values.